A novel approach for sulfur-doped hierarchically porous carbon with excellent capacitance for electrochemical energy storage. Issue 86 (10th October 2016) - Ji, Hongmei; Wang, Ting; Liu, Yang; Lu, Chunliang; Yang, Gang; Ding, Weiping; Hou, Wenhua
Abstract : A novel approach was developed to accomplish S-doping and pore-creation simultaneously, leading to the formation of hierarchically porous S-doped carbon with enhanced capacitance. Abstract : A novel approach for hierarchically porous S-doped carbon was developed. Owing to the obviously reduced particle size and greatly enhanced meso-/macropores, electronic conductivity and surface polarity as well as the active sites available for Faradaic reactions, the resultant S-doped carbon electrode shows an excellent supercapacitor performance.